Peran Guru Dalam Menerepkan Disiplin Belajar Siswa - Inom Nasution; Ainun Hidayasha; Mawaddah Tun‘nisa; Affiq faeyza; Syarifah Tussuriyani Hsb; Zaidan kholis (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Teachers as the main component in the learning process play an important role. The role of the teacher is to educate, teach, guide and train and motivate students, so that they are able to be disciplined, so that they are successful in pursuing education. Teachers have a big role in educating students because teachers can train students' discipline at school so that good character is formed in children. The aim of this research is to explain the role of teachers in implementing student discipline at MIN 1 Medan. This research uses qualitative methods with descriptive research type. Data collection techniques in this research were carried out by observation, interviews and documentation with MIN 1 Medan teachers. The results of the research show that the role of teachers in applying learning discipline to students at MIN 1 Medan is good because with teachers being role models of discipline for their students, the teachers there have displayed and provided examples of good attitudes in implementing students' disciplinary character.